Students' Perception on Learning Physical Education, Sports And Health - Daharis; Yulianti, Mimi; Cendra, Romi; Yudha, Ian Viandra (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
The aim of this research is to determine students' perceptions of learning physical education, sports and health at SMP IT Insan Utama 2 Pekanbaru. This type of research is quantitative descriptive. The population in this study was a population of 86 students in grades VII - IX, the sampling technique was purposive sampling, namely sampling based on certain considerations, in this study the sample taken was the number of students who were present at the time of the research, namely 48 students, namely 55 .81% of the total population. The research instrument used was a Likert scale. Based on the research results, the conclusion obtained in this research is: students' perceptions of learning Physical Education, Sports and Health at SMP IT Insan Utama 2 Pekanbaru are included in the score range of 61-80% or in the strong category with a percentage of 72.93%.